Pengujian Aplikasi Penyewaan Lapangan Futsal Berbasis Dekstop dengan Metode Black Box Testing Menggunakan Teknik Boundary Value Analysis - Endar Nirmala; Aries Saifudin; Dilan Tri Ovandi; Rika Nursafitri; Wahyudin Wahyudi; Ziska Andris (Jurnal Informatika Universitas Pamulang, 2022)
This futsal application is an application design to assist the administration of payments and orders for a futsal business anywhere. With this application it becomes easier to order and pay for the application that was created. Technological developments continue to grow along with increasing industrial progress in various fields. In addition to functioning as a means of information, for industry players, technology is also useful as a means of branding or promoting the industry they are running. The initial stage in this test is checking the futsal field booking application by using netbeans. Then, it is continued with writing concentration which aims to collect information that supports and is related to how to collect writings, diaries, papers and readings related to the title of the exam. Next is a needs investigation carried out to complete this test. The next stage is to test the system. In the application there are several forms, including field reservations, field rentals, payments, reservations/tenants, name and telephone forms. In this test, it is tested on the field registration registration form. In the field registration form, the admin can add new information and data columns. Admin can also view and change the data fields that have been added previously. The final result that has been made in this test is that the Black Box with Boundary Value Analysis technique can help the most common way of making experiments and quality testing. The test results for the additional field structure are 100% effective. The creators suggest that further exploration in the trial period does not use only one testing technique, so the results can be much more valid